GrooVR: an open access virtual reality drumming application to improve pro-sociality using synchronous movement - Cross, Liam; Nixon, Wesley; Smith, Jack; Tseng, Chia-huei; Kitamura, Yoshifumi; Endo, Isamu; Savostijanovs, Juris; Atherton, Gray (Frontiers in Psychology, 2025)
Interpersonal synchrony can enhance social bonding, cooperation, and reduce negative biases, especially toward out-group members. However, studying social synchrony faces practical challenges. To address this, we introduce a customizable virtual reality (VR) application and report two experiments evaluating its effectiveness. In the first experiment, participants drummed either in sync or out of sync with a virtual partner matching their gender, age, and ethnicity. Synchronous drumming increased feelings of affiliation but did not influence pro-social behavior in an economic game. The second experiment involved Caucasian participants drumming with Middle Eastern avatars. Synchronous drumming not only increased trust and affiliation but also reduced prejudicial attitudes toward Middle Eastern refugees. These findings suggest that virtual synchrony can strengthen social bonds and decrease bias, offering both theoretical insights and practical applications.